Complex Discourse Production in Persons with Mild Dementia: Measures of Richness of Vocabulary - Deepa M.S.; Shyamala K.C. (Journal of All India Institute of Speech and Hearing, 1970)
Dementia is characterized by the breakdown of intellectual and communicative functioning accompanied by personality change (DSM IV, American Psychiatric Association, 1994).Differentiating mild dementia from normal cognition in aging is a compelling social, clinical, and scientific concern. The present study aimed to determine whether a complex discourse production task distinguished normal older adults from adults with dementia with the measures of richness of vocabulary. Considered for the study were 10 healthy elderly adults and 10 persons with mild dementia. Spontaneous, conversational speech in dementia participants and healthy elderly was analyzed using three linguistic measures of richness of vocabulary. These were evaluated for their usefulness in discriminating between healthy and persons with dementia. The measureswere, type token ratio (TTR), Brunet's index (W) and Honore's Statistic (R). Results suggest that these measures offer a sensitive method of assessing spontaneous speech output in dementia. Comparison between dementia and healthy elderly participants demonstrates that these measures discriminate well between these groups. These findings also suggest that performance on a complex elicited discourse production task uncovers subtle differences in the abilities of persons with dementia (mild) such that measures of length and quality differentiated them from individuals with normal cognition. This method serves as a diagnostic and prognostic tool and as a measure for use in clinical trials.